Bartonella henselae as a cause of blood culture-negative endocarditis: a case report - Jana Rejc Marko; Nina Erjavc (Zdravniški Vestnik, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false SL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Keywords: Culture-negative endoccarditis, Bartonella spp., Bartonella henselae ABSTRACT: Background: Bartonella henselae was identified as an important cause of culture negative endocarditis, which represent 13-31 % of all infective endocarditis. Case report: We present a case of a 32-years old patient with congenital aortic stenosis diagnosed with infective endocarditis caused by B. henselae. Due to the slow progression of the illnes the patient was diagnosed only after a long diagnostic work up. We identified the causing organism as B. hensalae serologicaly. The microorganism has become in the last decade known as an important causative agent of hemoculture negative endocarditis. The patient needed antibiotic and surcical treatment, the outcome was good. Conclusions: Patient with relapsing episodes of fever need to have performed not only TTE but also TEE which has higher sensitivity for diagnosis of IE. In patients with IE with negative blood cultures, serology for most important causative agents has to be made. <span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: .5pt; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->